Što su donijeli novi pristupi knjižničnoj arhitekturi u 21. stoljeću? - Aparac-Jelušić, Tatjana (Knjižnica, 2019)
The aim of the paper is to discuss theoretical foundations of library architecture in the 21st century. The emphasis is on elements that have introduced changes and a move toward new approaches in designing library buildings, and principles that remain as foundation of library architecture from Faulkner-Brown to today. Special attention is given to functional approaches and new concepts in architectural design of contemporary libraries.
Keywords: 21.st.; arhitektura; funkcionalni pristopi; knjižnice; projektiranje